Methodology for load compensation in four-wire electrical power systems based on instantaneous sampling - de Oliveira, L C O; Neto, M C B (Institute of Electrical and Electronics Engineers (IEEE), 2000)
This work describes a methodology for power factor control and correction of the unbalanced currents in four-wire electric circuits. The methodology is based on the insertion of two compensation networks, one wye-grounded neutral and other in delta, in parallel to the load. The mathematical development has been proposed in previous work [3]. In this paper, however, the determination of the compensation susceptances is based on the instantaneous values of load currents. The results are obtained using the MatLab-Simulink enviroment